Model Pembelajaran Predict, Observe, Explain (POE) Terhadap Keterampilan Proses Sains Siswa Pada Materi Larutan Elektrolit dan Nonelektrolit - Mutiyah, Citra; Irawan, Dedi; Bahriah, Evi Sapinatul (Center of Community Service (PPM), Institute for Research and Community Services (LP2M) UI, 2020)
Abstract:This study aims to determine the effect of Predict, Observe, Explain (POE) learning models on students' science process skills on electrolyte and non-electrolyte solution materials. The subjects in this study were students of class X at SMA Negeri 89 East Jakarta in the academic year 2013/2014. The research method applied was a quasi-experimental design with nonequivalent control group design. Samples were taken by purposive sampling and divided into 2 groups, namely the experimental group and the control group. The instruments used in this study were essay test instruments and observation sheets. Data analysis techniques were obtained using the